ANALISIS MODAL KERJA INDUSTRI KECIL USAHA PERTUKANGAN KAYU DAN USAHA LAS DI KOTA PALEMBANG - SUHARTINI KARIM; UMAR HAMDAN AJ (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
The aims of this research are to observe and analyze working capital of small industry  woodworking and welding businesses in Palembang City. This research will apply survey method by using20 small scale industries- holders as sample respondents. Data will  analyzed by using quantitative and qualitative methods, such as statistical frequency and cross tabulation, financial ratio analysis, and caculating working capital requirement.Research findings are 1)  the firm samples have simple organization and management. 2) They have no adequate working capital. 3) They have  problem in  increasing of raw materials costs, and operating expenses. The writer suggests that the firms have to obtain additional working capital to support the future sales.